Nanomedicine: is it lost in translation?. (2nd March 2018) - Greish, Khaled; Mathur, Aanchal; Bakhiet, Moiz; Taurin, Sebastien
By the end of 2017 more than 200, 000 scientific research articles had been published about nanomedicine. Out of this vast number only a few of the reported nanoconstructs reached clinical trials for various applications, including the diagnosis and treatment of several cancers, and the treatment of infections and other non-cancerous diseases. 30 years after the pioneering work in this field of research, the low product yield at the end of research pipeline leads to a question that is asked by many: 'had nanomedicine been lost in translation?' In this review, we will discuss the landscape of nanomedicine regarding cancer treatment and miscellaneous applications as well as some obstacles toward full utilization of this powerful therapeutic tool and suggest a few solutions to improve the current translational value of nanomedicine research.